An unquiet mind - Jamison, Kay R. (A.A. Knopf, 1995)
From Kay Redfield Jamison - an international authority on manic-depressive illness, and one of the few women who are full professors of medicine at American universities - a remarkable personal testimony: the revelation of her own struggle since adolescence with manic-depression, and how it has shaped her life. Vividly, directly, with candor, wit, and simplicity, she takes us into the fascinating and dangerous territory of this form of madness - a world in which one pole can be the alluring dark land ruled by what Byron called the "melancholy star of the imagination," and the other a desert of depression and, all too frequently, death. A moving and exhilarating memoir by a woman whose furious determination to learn the enemy, to use her gifts of intellect to make a difference, led her to become, by the time she was forty, a world authority on manic-depression, and whose work has helped save countless lives.